2020
DOI: 10.5539/jas.v13n1p73
|View full text |Cite
|
Sign up to set email alerts
|

A probit Analysis of Determinants of Adoption of Improved Sorghum Technologies Among Farmers in Tanzania

Abstract: The adoption of improved sorghum technologies by smallholder farmers is still low in Tanzania. Many farmers fail to acquire quality inputs due to different underlying reasons. This article analyzes factors underlining the adoption of improved technologies among sorghum farmers in Tanzania and evaluates profitability of grain production. A total of 212 individual farmers were interviewed through structured questionnaires from nine districts. Data were analyzed using descriptive statistics, probit regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…From profit and utility maximation theory perspective, most of econometric models used are binary ones (i.e probit and logit model) since adoption and market participation decisions are dichotomous choice (yes = 1/no = 0). Furthermore, gross margin analysis was also used as a proxy for profitability analysis in this study ( Rao et al.,2017 : Engwali et al.,2019 ) to show the profitability of using improved varieties ( Kimbi et al., 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…From profit and utility maximation theory perspective, most of econometric models used are binary ones (i.e probit and logit model) since adoption and market participation decisions are dichotomous choice (yes = 1/no = 0). Furthermore, gross margin analysis was also used as a proxy for profitability analysis in this study ( Rao et al.,2017 : Engwali et al.,2019 ) to show the profitability of using improved varieties ( Kimbi et al., 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the context of this study, farmers are more likely to adopt rainwater harvesting if it maximizes their utility subject to constraints related to the farmers. Studies from Asia and some African countries have shown that the adoption of rainwater harvesting is influenced by different contextual factors (Li et al, 2020;Llewellyn and Brown, 2020;Kimbi et al, 2021).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…However, the linear probability model is criticized to predict probabilities outside the range of 0 to 1. Hence, most studies on the adoption of agricultural innovations apply either logit or probit regression models (Kimbi et al, 2021). These models tend to generate similar results.…”
Section: Empirical Model Specificationsmentioning
confidence: 99%
“…From profit and utility maximation theory perspective, most of econometric models used are binary ones (i.e probit and logit model) since adoption and market participation decisions are dichotomous choice (yes ¼ 1/no ¼ 0). Furthermore, gross margin analysis was also used as a proxy for profitability analysis in this study (Rao et al,2017: Engwali et al, 2019 to show the profitability of using improved varieties (Kimbi et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%